Perlindungan Hukum Terhadap Pihak yang Dirugikan Dalam Wanprestasi - Rahayu, Cantika Tresna; Adam, Chelsea Kairadinda; Amalia, Firda; Vazkya, Ni Komang Revalina Senandung; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Legal protection for parties harmed by default is an important issue in contract law. Default, referring to the failure of one party to fulfill obligations in a contract, often results in significant losses for the aggrieved party. This study aims to analyze the types of legal protections available for the harmed party and the dispute resolution mechanisms that can be applied. Using a qualitative approach, this research explores both preventive and repressive aspects of legal protection, including the creation of clear and specific agreements as well as legal actions that can be taken after a default occurs. The findings indicate that while various protective mechanisms exist, there are still many challenges in their implementation. Therefore, there is a need to enhance awareness of the importance of legal protection and enforcement of the rights of harmed parties to create justice in contractual relationships.